Do Cultural Differences Impact on Intellectual Property Protection in the United States and China? - Chen, Meihua; Jin, Tao (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
In a knowledge economy, intellectual property is highly related to core competency of an organization. Without proper protection, the competitive advantage is vulnerable to imitation and counterfeiting. Intellectual property protection can be seen as information and knowledge activities that are taken to prevent trademark, patent, copyright, and trade secret infringement. Between the United States and China, there is an intense and enduring controversy on intellectual property protection. Many previous relevant studies on this issue adopted a legal and governance approach, rarely focusing on the effect of cultural differences on these information and knowledge practices. This paper reports the theoretical exploration portion of an on-going empirical research on the cultural influences that impact intellectual property protection in the two countries, aiming to draw some implications for the field of knowledge management.